KOMPARASI KUALITAS INFORMASI DAN ASIMETRI INFORMASI SEBELUM DAN SESUDAH ADOPSI IFRS DI INDONESIA - Sugi Suhartono, Yustina Triyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
This research aims to provide empirical evidence relating to information quality and information asymmetry before and after IFRS adoption. This study uses value relevance as a proxy of financial report information quality and bid ask spread as a proxy of information asymmetry. The sample in this study uses secondary data 372 companies listed in Indonesia Stock Exchange form 2008 to 2016. This study uses Multiple Linear Regression method, Chow Test and Paired-Sample t Test Difference Test. The results showed that after IFRS adoption there was an increase in the quality of financial report information and a decrease in information asymmetry.Keywords: IFRS, Quality of information, Information asymmetry